2019
DOI: 10.3390/toxins11010026
|View full text |Cite
|
Sign up to set email alerts
|

Vampire Venom: Vasodilatory Mechanisms of Vampire Bat (Desmodus rotundus) Blood Feeding

Abstract: Animals that specialise in blood feeding have particular challenges in obtaining their meal, whereby they impair blood hemostasis by promoting anticoagulation and vasodilation in order to facilitate feeding. These convergent selection pressures have been studied in a number of lineages, ranging from fleas to leeches. However, the vampire bat (Desmondus rotundus) is unstudied in regards to potential vasodilatory mechanisms of their feeding secretions (which are a type of venom). This is despite the intense inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…Cumulative concentration–response curves to venom (1 ng/mL–1 µg/mL) were constructed in vessels pre-contracted submaximally to ~50% F max with titrated concentrations of U46619 (0.01–0.2 µM). Responses to venom were obtained in endothelium-intact mesenteric arteries pre-incubated for 30 min with either 30 mM K + [45], mepyramine (0.1 µM), L-NAME (100 µM) [44], TEA (1000 µM) [46], iberiotoxin (0.1 µM), apamin (0.1 µM), TRAM-34 (1 µM), 4-aminopyridine (1000 µM) [44], glibenclamide (10 µM) [47,48] or RN-1734 (10 µM). Cumulative concentration-response curves were also constructed to venom alone (1 ng/mL–1 µg/mL) or GSK1016790A in the presence and absence of RN-1734 (10 µM).…”
Section: Methodsmentioning
confidence: 99%
“…Cumulative concentration–response curves to venom (1 ng/mL–1 µg/mL) were constructed in vessels pre-contracted submaximally to ~50% F max with titrated concentrations of U46619 (0.01–0.2 µM). Responses to venom were obtained in endothelium-intact mesenteric arteries pre-incubated for 30 min with either 30 mM K + [45], mepyramine (0.1 µM), L-NAME (100 µM) [44], TEA (1000 µM) [46], iberiotoxin (0.1 µM), apamin (0.1 µM), TRAM-34 (1 µM), 4-aminopyridine (1000 µM) [44], glibenclamide (10 µM) [47,48] or RN-1734 (10 µM). Cumulative concentration-response curves were also constructed to venom alone (1 ng/mL–1 µg/mL) or GSK1016790A in the presence and absence of RN-1734 (10 µM).…”
Section: Methodsmentioning
confidence: 99%
“…CRISPs play a wide variety of roles in non-venomous tissues, and their function appears likewise diverse in venoms (67). Vampire bats use a calcitonin gene-related peptide (CGRP) as a vasodilator (68), and this peptide is likewise expressed in human and rat saliva, as well as other tissues (69,70). As CGRPs are potent vasodilators, their co-option into bat venom should enhance its function.…”
Section: Stage 1: Exaptation Of Salivary Enzymes Particularly Kallikmentioning
confidence: 99%
“…72 The species Desmodus rotundus has been studied due to the antithrombolysinic action of draculin presenting relaxing vessel efficacy and facilitating blood flow in vascular diseases in vivo. 73 Studies of this vampire bat-derived plasminogen activator, more recently referred to as desmoteplase, revealed that this protease has become attractive for the clinical development of patients with ischemic stroke. 74 Phylogenetic analyses, proposed by Latinne 75 show that the exchange between families and bat genera occurred more commonly in the Rhinolophidae family and in the genus Rhinolophus, host exchanges were more frequent and in host letons in alpha-CoVs and beta-CoVs, presenting a probable origin for SARS-CoV-2 in Rhinolophus spp bats.…”
Section: Records Of Phylogenetic Analyses Performed By Researchers Inmentioning
confidence: 99%